DETEKSI PLAT NOMOR KENDARAAN PADA UNIVERSITAS XYZ MENGGUNAKAN METODE MSER (MAXIMALLY STABLE EXTREMAL REGIONS) - Andhika Wisnu Widyatama; Kusrini Kusrini; Sudarmawan Sudarmawan (TEKNIMEDIA: Teknologi Informasi dan Multimedia, 2022)
The increasing number of students at XYZ Yogyakarta University every year is balanced with the number of vehicles used, it is necessary to pay attention to developing efficient intelligence and also a safe transportation system. Several studies of plate recognition methods have shown promising performance, but some methods may have weaknesses in situations of plate position and orientation variations, lighting, background, and non-plate objects. This research uses the Maximally Stable Extremal Regions (MSER) ​​method which is a keypoint search method based on the extremal region. The MSER method has been identified as one of the best region detectors due to its resistance to changes in viewing angle, scale, and exposure, as well as sensitivity to image blur. From the results obtained a detection rate of 80% can detect vehicle number plates well.